Comparison of methods on detection of Bisphenol A (BPA) / Mohamad Zaidi Zakaria - Zakaria, Mohamad Zaidi (2016)
Bisphenol A (BPA) is one of the main component in many plastic product that might be cancerous to human at certain level of consumption. Its endocrine disruptive chemical (EDC) characteristic my cause various kind of health defect such as heart disease, brain malfunction, reproductive disorder and so on at certain level of consumption. Several types of plastic sample from (1-7) number of classification are tested for BPA content which the sample are subjected to high temperature for leaching purposes. There are 3 methods for BPA detection in plastic which are the Iron (iii) chloride test, High performance Liquid Chromatography (HPLC) analysis and Gas Chromatography Mass Spectrometry (GCMS) analysis. From the iron (iii) chloride test the result show no significant finding based on the color of the cotton swab which remain as yellow color for every sample after triplicate run. From HPLC test, some sample such as mineral water bottle, toy gun, sandwich bag, baby bottle, and plastic cup show positive BPA content based on the BPA standard marker. From GCMS analysis the result shows that mineral water bottle, talcum bottle, toy gun, baby bottle, and CD is positive BPA. By comparison HPLC analysis is the best methodology to detect BPA content in plastic